Characterisation of sol–gel method synthesised MgZnFe2O4 nanoparticles and its cytotoxic effects on breast cancer cell line, MDA MB-231 in vitro - Nordin, Noraini; Kanagesan, Samikannu; Zamberi, Nur Rizi; Yeap, Swee Keong; Abu, Nadiah; Subramani, Tamilselvan; Hashim, Mansor; Mohammed Alitheen, Noorjahan Banu (The Institution of Engineering and Technology, 2017)
In this study, nanocrystalline magnesium zinc ferrite nanoparticles were successfully prepared by a simple sol–gel method using copper nitrate and ferric nitrate as raw materials. The calcined samples were characterised by differential thermal analysis/thermogravimetric analysis, Fourier transform infrared spectroscopy and X-ray diffraction. Transmission electron microscopy revealed that the average particle size of the calcined sample was in a range of 17–41 nm with an average of 29 nm and has spherical size. A cytotoxicity test was performed on human breast cancer cells (MDA MB-231) and (MCF-7) at various concentrations starting from (0 µg/ml) to (800 µg/ml). The sample possessed a mild toxic effect toward MDA MB-231 and MCF-7 after being examined with MTT (3-[4, 5-dimethylthiazol-2-yl]-2, 5 diphenyltetrazolium bromide) assay for up to 72 h of incubation. Higher reduction of cells viability was observed as the concentration of sample was increased in MDA MB-231 cell line than in MCF-7. Therefore, further cytotoxicity tests were performed on MDA MB-231 cell line.